Patterns in the Use of Cooperative Agents for Innovation in the Brazilian Manufacturing Industry - Diego de Queiroz Machado; José Ednilson de Oliveira Cabral; Fátima Regina Ney Matos (BBR: Brazilian Business Review)
This research aims to identify clusters of business segments for the use of cooperative agents for the development of innovations in the manufactu ring industry of Brazil. Data from 2008 of Pesquisa de Inovação Tecnológica - PINTEC (Surve y of Technological Innovation) were analyzed by cluster analysis technique, in order to facilitate the grouping of industries present in the PINTEC’s data from the patterns of cooperati on shown between companies and other agents of innovation. In this sense, there was a la rger low valuation of the external cooperation agents, mainly universities and researc h centers, indicating an innovation model that is still far from the concept of open innovati on. On the other hand, the information networks and consumers and suppliers stood out as i mportant innovation agents.